2003
DOI: 10.1038/sj.ijo.0802389
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance induces hyperleptinemia, cardiac contractile dysfunction but not cardiac leptin resistance in ventricular myocytes

Abstract: Insulin resistance is a metabolic syndrome commonly seen in obesity. Leptin, the obese gene product, plays a role in the regulation of cardiac function. Elevated leptin levels have been demonstrated under insulin-resistant states such as obesity and hypertension, although their role in cardiac dysfunction is unknown. This study was designed to determine the impact of prediabetic insulin resistance on leptin levels and leptin-induced cardiac contractile response. Whole-body insulin resistance was generated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 25 publications
10
45
0
Order By: Relevance
“…Data from our present study revealed that ventricular myocytes from sucrose-fed mice exhibited depressed PS amplitude, reduced ±dL/dt and prolonged TR 90 associated with normal TPS and HWD. Most of these data are consistent with our previous findings using a similar hyperinsulinaemic insulin-resistance model in rats [6,26]. The fact that Fig.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Data from our present study revealed that ventricular myocytes from sucrose-fed mice exhibited depressed PS amplitude, reduced ±dL/dt and prolonged TR 90 associated with normal TPS and HWD. Most of these data are consistent with our previous findings using a similar hyperinsulinaemic insulin-resistance model in rats [6,26]. The fact that Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the previous findings [5,6,19], sucrose induced hyperinsulinaemia, which was not affected by the catalase transgene (Table 1). Following acute i.p.…”
Section: Experimental Animalssupporting
confidence: 93%
See 3 more Smart Citations